2006
DOI: 10.1007/s10529-005-4683-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distributions of Metal Ions and Taxol of Taxus cuspidata Cells Immobilized on Polyurethane Foam

Abstract: Distinct spatio-temporal variations of metal ions and Taxol production were observed for Taxus cuspidata cells immobilized on polyurethane foam. The Taxol content in the inner foam layer reached 215 microg g(-1) at day 30, which was 40-fold higher than that in the outer foam layer, and the Ca2+ and Mg2+ contents were 5.3 and 3.7 times higher, while the K+ content was 5.5 times lower. Thus higher intracellular Ca2+ and Mg2+ contents and lower intracellular K+ content may favor the Taxol biosynthesis in immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The post-synthesis method, used to protect and control the cell environment, is based on the adsorption of cells on different pre-formed substrates such as polyurethane foams, [55][56][57][58] nylon foams, 59 fiberglass, 60 loofa (Luffa cylindrica) sponges 61,62 and inverted colloidal crystals. 63 Post-formation avoids the need to consider the biocompatibility of the precursors used in materials synthesis as long as the resultant host structure is free from cytotoxins.…”
Section: Post-synthesis Immobilisationmentioning
confidence: 99%
“…The post-synthesis method, used to protect and control the cell environment, is based on the adsorption of cells on different pre-formed substrates such as polyurethane foams, [55][56][57][58] nylon foams, 59 fiberglass, 60 loofa (Luffa cylindrica) sponges 61,62 and inverted colloidal crystals. 63 Post-formation avoids the need to consider the biocompatibility of the precursors used in materials synthesis as long as the resultant host structure is free from cytotoxins.…”
Section: Post-synthesis Immobilisationmentioning
confidence: 99%
“…Moreover, the pore size has complex effects on the activity, stability, and recycling properties of hybrid materials. [97] This approach exploits the natural tendency of many microorganisms, algae, and plant cells to attach to surfaces and grow upon them. [79] Takahashi et al reported that a tight fit inside the pores is also essential to increase stability and sufficiently protect the proteins.…”
Section: Adsorptionmentioning
confidence: 99%
“…[92,93] In the case of organelles and whole living cells, immobilization can also be achieved through an adsorption process on different pre-formed substrates such as loofa sponges, [94] fiberglasses, [95] glass discs, [96] and polyurethane foams. [97] This approach exploits the natural tendency of many microorganisms, algae, and plant cells to attach to surfaces and grow upon them. In comparison to proteins, the immobilization of organelles or cells is more delicate.…”
Section: Adsorptionmentioning
confidence: 99%